Increased frequencies of activating natural killer receptors are associated with liver injury in individuals who do not eliminate hepatitis C virus - Paladino, Natalia (2007)
This study was designed to investigate the role of KIR genes in the outcome of HCV infection. In patients who cleared the virus (HCV RNA-) we found a decrease of 2DL2 (p=0.04), and 2DS2 (p=0.014) accompanied by an increase of 2DS5 (p=0.04). Those RNA+ patients with elevated levels of hepatic transaminases (HCV RNA+ elevatedALT) showed an increased frequency of 2DS3 (p=0.018). Additionally, in cirrhotic patients we found an increased frequency of individuals having two copies of 3DS1 and HLA-Bw4 (p=0.016). We conclude that higher NK cytotoxicity might be associated with a worse progression of the HCV infection.